2002
DOI: 10.1094/mpmi.2002.15.8.780
|View full text |Cite
|
Sign up to set email alerts
|

Extending Chestnut Blight Hypovirus Host Range Within Diaporthales by Biolistic Delivery of Viral cDNA

Abstract: Biolistic bombardment was used to successfully transform three phytopathogenic fungal species with an infectious cDNA clone of the prototypic hypovirus, CHV1-EP713, a genetic element responsible for the virulence attenuation (hypovirulence) of the chestnut blight fungus, Cryphonectria parasitica. The fungal species included two strains each of C. parasitica and Valsa ceratosperma, as well as one strain of Phomopsis G-type (teleomorph Diaporthe Nitschke); all are members of the order Diaporthales but classified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…Some hypovirulence-associated mycoviruses from B. cinerea and its related species Botrytis porri have been isolated and characterized (10,54,57), but these Botrytis viruses are unlikely to be used for control of diseases caused by these fungi under field conditions because they are easy to be eliminated via asexual propagation (see below). Expansion of the host range of mycoviruses has been accomplished for many fungus-mycovirus systems (7,8,24,(58)(59)(60)). …”
Section: Discussionmentioning
confidence: 99%
“…Some hypovirulence-associated mycoviruses from B. cinerea and its related species Botrytis porri have been isolated and characterized (10,54,57), but these Botrytis viruses are unlikely to be used for control of diseases caused by these fungi under field conditions because they are easy to be eliminated via asexual propagation (see below). Expansion of the host range of mycoviruses has been accomplished for many fungus-mycovirus systems (7,8,24,(58)(59)(60)). …”
Section: Discussionmentioning
confidence: 99%
“…However, experiments using infectious cDNA clones or synthetic transcripts have shown that the prototype hypovirus replicates in fungal species of the same family (63) or a different one within the same order as that of its natural host, the chestnut blight fungus C. parasitica (64). The virion transfection protocol has also provided chance to expand the host range of mycoviruses, such as RnPV1 and MyRV3 (65).…”
Section: Discussionmentioning
confidence: 99%
“…1). This approach will be applicable to the assessment of RNAi activation patterns in different fungi that can support CHV1 replication (31,32). Given the large number of viruses hosted by C. parasitica (14,33), the reporter fungal strain (Fig.…”
Section: Saga Mediates Virus-responsive Induction Of Rnai Key Genesmentioning
confidence: 99%